Checklist development for assessing the dental students\' clinical skills in oral and maxillofacial medicine course and comparison with global rating - Arash Mansourian; Shiva Shirazian; Mohammad Jalili; Mehdi Vatanpour; Leila Pour Momen Arabi (Tehran University of Medical Sciences, 2017)
Background and Aims: The objective of this study was the development of a checklist for assessment of students’ clinical skills in the clinical oral medicine. The second aim was the assessment of stake holders’ satisfaction of this checklist in comparison to the routine global rating method. Materials and Methods: The checklist was developed in an expert panel sessions and the validity and reliability of checklist were assessed by CVI and test-retest method, respectively. All students (n=66) were assessed in 2 groups, one with developed checklist and another with global rating. At the end of the session, the satisfaction’s level of staff and students were analysized using Wilcoxon and Mann-Whitney test and the mean scores of students were analysized using Paired T test. Results: Content validity index (CV I) of checklist was 0.88. Reliability of checklist confirmed with high correlation coefficient (0.9). Staffs’ satisfaction had no significant difference between the two methods (Wilcoxon P=0.06). The mean score of students who assessed by checklist was higher than global rating with no significant differences (P=0.06). Conclusion: Regarding the higher students’ satisfaction from checklist and more attention to component of assessment and more objectivity of this method and also higher score in checklist, it seems that the use of a checklist is more proper method for assessing the students’ clinical skills.